Respuesta :

Answer:

Simplifying

5x + 0(x + y) + -3y + 14 + -3(y + -1x) = 0

Anything times zero is zero.

5x + 0(x + y) + -3y + 14 + -3(y + -1x) = 0

Reorder the terms:

5x + 0 + -3y + 14 + -3(-1x + y) = 0

5x + 0 + -3y + 14 + (-1x * -3 + y * -3) = 0

5x + 0 + -3y + 14 + (3x + -3y) = 0

Reorder the terms:

0 + 14 + 5x + 3x + -3y + -3y = 0

Combine like terms: 0 + 14 = 14

14 + 5x + 3x + -3y + -3y = 0

Combine like terms: 5x + 3x = 8x

14 + 8x + -3y + -3y = 0

Combine like terms: -3y + -3y = -6y

14 + 8x + -6y = 0

Solving

14 + 8x + -6y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.

14 + 8x + -14 + -6y = 0 + -14

Reorder the terms:

14 + -14 + 8x + -6y = 0 + -14

Combine like terms: 14 + -14 = 0

0 + 8x + -6y = 0 + -14

8x + -6y = 0 + -14

Combine like terms: 0 + -14 = -14

8x + -6y = -14

Add '6y' to each side of the equation.

8x + -6y + 6y = -14 + 6y

Combine like terms: -6y + 6y = 0

8x + 0 = -14 + 6y

8x = -14 + 6y

Divide each side by '8'.

x = -1.75 + 0.75y

Simplifying

x = -1.75 + 0.75y

Step-by-step explanation:

I'm not sure if the graph or equation answers your question or not sorry if I did it wrong.

Ver imagen MoonieStardust
Ver imagen MoonieStardust
ACCESS MORE